Automatic Local Coordinates Evaluating and automating methods to estimating 3D coordinates with respect to a specific Datum - Couto, Rafael Gonçalves (2019)
Made available in DSpace on 2019-12-11T16:51:37Z (GMT). No. of bitstreams: 1 5220_10667.pdf: 3247858 bytes, checksum: a1122cbc4ba9002161ada6fdbbe160a0 (MD5) Previous issue date: 2016-11-10